2E.005 Toxicovigilance for suicide prevention following Internet promotion of sodium nitrite. (14th March 2021) - Brown, Jared; Berling, Ingrid; Jiranantakan, Thanjira; Buckley, Nicholas; Dawson, Andrew
Abstract : Background: There are limited epidemiological studies on emerging trends in suicide methodology relating to Internet promotion of toxic substances. We investigated time trends and demographic characteristics of deliberate self-poisonings with sodium nitrite/nitrate following Internet promotion for euthanasia in 2017 and a cluster of poisonings. Methods: Retrospective observational study of the National Coronial Information System (2000 – June 2020), Poisons Information Centres, toxicology services (2004 – June 2020) and a scoping review including Embase and MEDLINE (2000 – June 2020) for deliberate self-poisonings with sodium nitrite/nitrate. We examined survival, date, gender, age, setting, geographical location, history of a terminal or psychiatric illness, product. Results: We identified 66 deliberate self-poisonings, who were mostly male (65%) with a wide age distribution (median: 44 years; IQR: 24–66 years; range: 16–92 years; mode: 20–29 years). The majority had a fatal outcome (80%). A sudden and sustained step-increase in poisonings was seen from September 2017 (and the first death). Most cases (83%) had a psychiatric illness and no terminal illness (91%). There were 33 unique cases (mostly young adults) identified in the scoping review from eight countries. Conclusions: The promotion of suicide methodology was associated with a dramatic change in harms from sodium nitrite/nitrate in the past two decades. The signal generated by poisons centre cases was confirmed using national coronial data and pooled poisoning data. Learning Outcomes: State public health actions to date have focused on means restriction, improved antidote stocking and clinical education. National and international collaboration is needed for monitoring promoted lethal substances.